Design and Build of Broom Handle Cutter and Shaper to Improve Production Efficiency and Working Time: Rancang Bangun Alat Pemotong dan Pembentuk Gagang Sapu untuk Meningkatkan Efisiensi Produksi dan Waktu Kerja - Putra, Davin Herdiansyah; Widiasih, Wiwin (Universitas Muhammadiyah Sidoarjo, 2024)
This study designs a cutting and shaping tool for broom handles to improve production efficiency and reduce operator workload at Victory 2 Singa. The main issues include slow manual production processes, high costs due to the use of nails, and non-ergonomic tool designs. The proposed solution involves designing a new tool using Quality Function Deployment (QFD). Through QFD, customer requirements such as comfort, safety, durability, affordability, and ease of use are analyzed and translated into technical attributes for the tool. The results of the research show that the designed tool can meet the primary priorities, namely providing precise cutting results, ergonomic handle shapes, and an efficient working process.